Caring leadership and head nurses' performance in three selected SPC-managed hospitals - Dayrit, Mary Wilfrid (2000)
Changes brought about by advance technology, globalization and empowerment have affected directly the health care ministry. People demand quality care with less cost, and want to be treated in a personal way. To balance these demands, health care institution are finding ways to meet the expectations of the health consumers. The nursing profession is experiencing crises of confidence that were brought about by these constraints. Effective leadership is crucial at this time to promote caring which is considered an essential component of nursing practice. It is imperative that the influence of caring leadership to job performance be determined. The head nurse being an essential person in the ward should be aware how caring can balance these constraints.This study was conducted to determine the caring leadership and job performance of head nurses within the Paulinian vision-mission. The head nurses of three selected SPC-managed hospitals were the main foci. Assessment of the staff nurses and self-assessment of the head nurses were examined to see the relationship of caring leadership and job performance of head nurses. The relation of age, religious affiliation, educational attainment, number of years of experience, and continuing education updates to job performance were also examined.The study utilized a descriptive non-probability correlational design to see how the caring leadership relates to job performance. A combination of quantitative and qualitative data derived from the opinions of the head nurses and staff nurses formed the bases of the findings.The instrument on caring leadership measured the ability to bring out potential, compassion and commitment. The instrument on job performance measured the functions and responsibilities of the head nurses on the management of the unit, management of the personnel and management of patients through a 16-item questionnaire. Both sets of questionnaires are scaled in Likert choices of agree-disagree levels. These tools were pre-tested and items validated through reliability coefficient.Data were analyzed using descriptive and inferential statistics specifically, the contingency coefficient, a measure of association preset at p 0.05 level of confidence. Results show that caring leadership is correlated with job performance. This is significant at a 95 level of confidence with a direction that the more caring the leader, the more efficient or effective the performance of the head nurses. The head nurses' self-assessment on their caring leadership was synchronous with that of the staff nurses as well as on job performance. However, componentially, there are a few items where the two groups differed in scaling the values between the "all the time" and the "most of the time" categories. The difference of perception and experience of these two groups can be alluded to the thin line of demarcation between the "all the time" and "most of the time" scale. But when computed statistically, the values between the two groups run in the line of congruence.It was interesting to note that qualitatively, the variables of age, religious affiliation, civil status, educational attainment, number of years of work experience and continuing education updates were factors that contribute to caring and help them in the performance of duty. Statistically however, these variables did not have any significant correlational values with caring leadership nor with job performance.From the study, one recommendation stands up: to maintain and continue giving periodic fora, conferences and seminars on the vision-mission of SPC HCA because they contribute to the development of caring leadership leading to job performance efficacy. The instrument could be further validated to include items that affect staff nurses' field of duty and responsibility.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Nurse administrators; Care of the sick